English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

y=sqrt(x-6)
Next reverse the x and y to get: x=sqrt(y-6) now solve for y
x^2=y-6 so y=x^2+6 would be the inverse

2007-04-17 07:54:34 · answer #1 · answered by bruinfan 7 · 0 0

To find the inverse function, just swap y with x:
y = SQRT (x-6) becomes x = SQRT (y-6). Solving for y,
x² = y-6
y = x² + 6

2007-04-17 07:54:51 · answer #2 · answered by lil e 2 · 0 0

y = sqrt(x-6)
→ y² = x-6
→ x = y² + 6
So invf(y) = y² + 6

2007-04-17 07:55:04 · answer #3 · answered by Anonymous · 0 0

fedest.com, questions and answers